Millennial women preferences on bricks-and-mortar retail, in the era of digitalization: a study of fashion industry / Fatin Fasihah Mohd Zainy - Mohd Zainy, Fatin Fasihah (Faculty of Business and Management, 2018)
The purpose of this research is to identify the most significant variable to measure determinants of the millennial women preferences on bricks-and-mortar retail in the era of digitalization, which is a study of fashion industry. There are five independent variables to measure the millennial women preferences on bricks-and-mortar retail which are product assortment, product value, services provided, facilities and atmosphere. The research is being conducted towards millennial women which is in the range of age 20 years old to 38 years old. The information is gathered by distribution of questionnaire to the respondents by using convenience sampling. Out of 300 questionnaires distributed, only 128 questionnaires comply with the chriterion needed.